2014
DOI: 10.4081/ijas.2014.3239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural and Synthetic Antioxidants on Performance, Egg Quality and Blood Constituents of Laying Hens Grown Under High Ambient Temperature

Abstract: A total of 216 laying hens was kept at high ambient temperature (32±4°C, 60% relative humidity) from week 24 to 32 of age. Birds were divided in 8 treatments with 9 replicates of 3 hens each. The groups were fed the same basal diet and submitted to these dietary treatments: control, un-supplemented; green tea (GT), fed GT at 1 g/kg diet; brown marine algae (BMA), fed BMA at 1 g/kg diet; vitamin E (vit. E), fed vit. E at 300 mg/kg diet; GT+BMA, fed GT and BMA at 1 g/kg of each; GT+vit. E, fed GT and vit. E at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The resulting higher concentrations of serum calcium and phosphorus that were observed suggested that a GABA-producer could regulate the utilization of dietary calcium and phosphorus thereby alleviating defected egg caused heat-stress. Mashaly et al (2004) and Al-Harthi (2014) noted that high ambient temperature has a detrimental effect on laying performance, feed intake and feed conversion efficiency. Therefore, such high ambient temperature might cause a decline in activity of digestive enzymes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting higher concentrations of serum calcium and phosphorus that were observed suggested that a GABA-producer could regulate the utilization of dietary calcium and phosphorus thereby alleviating defected egg caused heat-stress. Mashaly et al (2004) and Al-Harthi (2014) noted that high ambient temperature has a detrimental effect on laying performance, feed intake and feed conversion efficiency. Therefore, such high ambient temperature might cause a decline in activity of digestive enzymes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heat-stress also affects growth rate, metabolism, immunity and reproduction of animals with an immeasurable impact ( Attia et al, 2011 ; Bloemhof et al, 2012 ; Nesamvuni et al, 2012 ). Although remarkable advances of feeding animals under high-density conditions have been widely applied ( Attia et al, 2006 ; Al-Harthi, 2014 ), heat-stress remains a costly issue for the animal production, especially for poultry as they lack sweat glands. Therefore, alleviating heat-stress is necessary for ensuring animal production in hot environments.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compound in those extracts were suspected playing important role to decrease heat stress impact. The most compounds in those extracts were as antioxidant (Al-Harthi 2014). Result of studies showed that there were several bioactive compounds played role as antioxidant in extract of S. tetrasperma (Kahkonen et al 1999;Khayyal et al 2005;El-Wakil et al 2015), turmeric rhizome (Gupta et al 2010;Mohana & Fadma 2014), and neem leaf .…”
Section: Figure 1 Average Daily Temperature ( O C) and Humidity (%) mentioning
confidence: 99%
“…The increasing consumption of healthy biological products requires investigation regarding the possibility of manipulating products of animal origin through dietary strategies. Increased carotenoid content is beneficial for human health, because carotenoids can be antioxidant and decreasing yolk cholesterol concentration (Al‐Harthi, ; Park, Upadhaya, & Kim, ; Zahroojian, Moravej, & Shivazad, ). Studies conducted by Zahroojian et al () suggested that use of 2.0% to 2.5% Spirulina in diets of laying hens over 60 days provided an aesthetically pleasing gem color without causing negative effects on performance.…”
Section: Introductionmentioning
confidence: 99%